Need Analysis of Student Worksheets Based on the Reading to Learn Approach in Teaching Reading Narrative Texts - Masitowarni Siregar; Rahmad Husein; Nora Ronita Dewi; Aldino Syahreza Simatupang; Dimas Hendrawan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
The 2018 Program for International Student Assessment survey released in 2019 showed that the reading literacy HOTS skills of Indonesian students was low where Indonesia was ranked 74th out of 79 countries. .To improve students HOTS reading literacy the Ministry of Research, Technology and Higher Education developed a Literacy Improvement Program at the National Junior High School level in 2021 using The Reading to Learn Approach. In this context, the objective of this research were to develop Students Worksheet Based on The Reading To Learn Approach to improve Students' Higher Order Thinking Skills on the Competence of Reading Narrative Texts. This research is part of research and development namely stage of needs analysis. The approach used was a qualitative approach. The study was conducted in MTsN 2 Medan. This study focused on the Needs analysis stage of teachers and students regarding the worksheet based on the reading to learn approach that is going to developed. The instrument to collect the data was interview The findings shows that most of the respondents expect the worksheet of Narrative Text should be developed based on their needs. They felt very hard to read the texts in English because the materials were irrellevant and not interesting. The students also confessed their current worksheet of Narrative Text was inappropriate for them and the process of learning was boring. Therefore, some of the aspects of learning also needed to be concerned such as learning style, learning technique, the way of doing the task, the length and topic of the texts, the situation of the class, the activities in the worksheet, and the difficulties of the students, in order to make the students easier to learn English.